Genotype adaptive patterns in spring wheat reveal drought-induced differentiation in root morphology - Frantová, Nicole; Guardia-Velarde, Lorena; Jovanović, Ivana; Weih, Martin (Frontiers in Plant Science, 2025)
Root morphology of agricultural crops plays a crucial role in crop resilience and early vigor, especially under the increasingly challenging environmental conditions associated with global climate change. This study aims to link root morphology types in six spring wheat genotypes to seedling establishment and stress responses under drought, suboptimal temperature (10°C), and low-temperature (7°C) conditions, providing insights for breeding programs aimed at enhancing early vigor. We quantified early vigor-related root traits (root length and diameter) using a non-invasive phenotyping method, while PPD-D1 and VRN-1 genes were analyzed to explore genetic influences on early root development. Results revealed considerable genotypic variation in root length. Stress at both 7°C and 10°C accentuated these differences, with the genotype ‘Dacke’ showing a reduced root length under low-temperature stress. Root diameter responses also varied significantly, with the genotypes ‘Bjarne’ and ‘Dacke’ developing thicker roots than ‘Diskett’ and ‘KWS Alderon’. Genotypic analysis revealed variations in PPD-D1 alleles, with ‘Bjarne’ carrying the photoperiod-insensitive allele (Ppd-D1a), which facilitated early root development as reflected in increased root length, while the other genotypes carried the photoperiod-sensitive allele (ppd-D1b). Genotyping of VRN-A1, VRN-B1, and VRN-D1 revealed allele combinations associated with a facultative growth habit in all genotypes that were originally classified as spring wheat. This suggests that these genotypes retain some responsiveness to vernalization, despite being used as spring types in practice. These findings highlight the genetic basis of early vigor and root adaptation under stress conditions, providing valuable insights for targeted breeding aimed at improving stress adaptation and resilience in variable climates.